2004
DOI: 10.1038/ng1289
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of a rice centromere uncovers active genes

Abstract: Centromeres are the last frontiers of complex eukaryotic genomes, consisting of highly repetitive sequences that resist mapping, cloning and sequencing. The centromere of rice Chromosome 8 (Cen8) has an unusually low abundance of highly repetitive satellite DNA, which allowed us to determine its sequence. A region of ∼750 kb in Cen8 binds rice CENH3, the centromere-specific H3 histone. CENH3 binding is contained within a larger region that has abundant dimethylation of histone H3 at Lys9 (H3-Lys9), consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
528
4
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 487 publications
(554 citation statements)
references
References 49 publications
19
528
4
3
Order By: Relevance
“…A more recent study has shown that centrochromatin has a histone modification pattern resembling that found in the downstream body of transcribed genes (Bergmann et al, 2011). Indeed, previous studies have detected transcription within rice centromeres (Nagaki et al, 2004), human neocentromeres (Saffery et al, 2003) and also within the alphoid array of a derivative of the synthetic HAC used in the present study (Iida et al, 2010). The chromatin profile at active kinetochores resembles the 'yellow' chromatin described in a recent paper (Filion et al, 2010).…”
Section: Discussionmentioning
confidence: 58%
“…A more recent study has shown that centrochromatin has a histone modification pattern resembling that found in the downstream body of transcribed genes (Bergmann et al, 2011). Indeed, previous studies have detected transcription within rice centromeres (Nagaki et al, 2004), human neocentromeres (Saffery et al, 2003) and also within the alphoid array of a derivative of the synthetic HAC used in the present study (Iida et al, 2010). The chromatin profile at active kinetochores resembles the 'yellow' chromatin described in a recent paper (Filion et al, 2010).…”
Section: Discussionmentioning
confidence: 58%
“…The distribution of CENH3-containing nucleosomes within the boundaries of centromeres is not well understood, although it appears to be discontinuous and interspersed with canonical nucleosomes (Blower et al 2002;Yan et al 2008). Some human neocentromeres and several plant centromeres contain genes embedded as islands within centromeres (Saffery et al 2003;Nagaki et al 2004;Gong et al 2012). While genes may closely border CENH3-containing nucleosomes, gene transcription is generally incompatible with CENH3 (Ketel et al 2009).…”
mentioning
confidence: 99%
“…Figure 4 ChIP analysis of custom-made antibodies compared to purchased antibodies. The three diagrams (A-C) display the relative enrichment (Y-axis) of corresponding histone modifications at specific sites, as indicated by the primer numbers described previously [19]. All selected primers sites correspond to the regions in the rice chromosome 8 centromere.…”
Section: Assessment Of Antibody Suitability For Immunoprecipitation Amentioning
confidence: 99%
“…We selected six primer pairs corresponding to the sequences near the centromere of rice chromosome 8 reported previously [19] for the ChIP assay. As shown in Figure 4, all three of our site-specific antibodies essentially displayed the same histone modification patterns as the antibodies purchased from the Upstate Company.…”
Section: Assessment Of Antibody Suitability For Immunoprecipitation Amentioning
confidence: 99%